Charitable Activities in Braniewo in the 1830s in the Light of the Evangelical Parish Chronicle - Jodkowski, Marek (Studia Warmińskie, 2022)
The pastor of the Evangelical parish in Braniewo, Rev. Leberecht Ferdinand Bock (years of office 1829-1845), edited its chronicle, in which he included information on charitable activities in the city. Above all, he emphasised the forms of assistance provided to the sick and those in need during the cholera epidemic of 1831. The Society for Relief and Rescue of the Sick (Verein zur Hilfsleistung und Rettung der Kranken) played an unquestionable role. After the end of the epidemic, the leading initiator of various forms of care for the people in need turned out to be the Board for the Poor (Armen-Direktorium), established a few years earlier, which was most probably one of the city’s deputations. From 1833 onwards, its meetings were held monthly. In 1839 the Society for the Assistance of the Poor (Hilfsarmenverein) was also founded, which intensified the support given to the people in need. Unfortunately, it ceased its activities rather quickly. As a result of numerous charitable initiatives undertaken in Braniewo, poverty and destitution were combated, vagrancy and begging were eliminated, and immediate (in some cases, even long-term) help for poor members of the local community was guaranteed.